Die Zukunft der europäischen Wirtschaftsintegration: Blockierte Vertiefung und wachsende Asymmetrie zwischen Frankreich und Deutschland - Schneider, Etienne; Syrovatka, Felix (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
After more than seven years of fiscal austerity and neoliberal structural reforms, the fundamental imbalances that led to the Eurozone crisis have remained unresolved and the project of European integration as such appears to be in the deepest crisis it has experienced so far. This has prompted the dominant forces in the EU to at least partially reconsider their present crisis management strategies, envisioning deeper integration towards a “Genuine Economic and Monetary Union” and outlining different future scenarios for the EU. While especially the Five President’s Report does acknowledge fundamental construction problems and crisis tendencies of the Economic and Monetary Union, the strategies to address them either fall tremendously short of this diagnosis or lack assertiveness. We argue that this inability to confront these crisis tendencies results from the growing economic and political asymmetry in the axis between France and Germany as the principal mechanism of compromise which undergirded previous cycles of European economic integration. At the bottom of this paralysis lies a gradual shift in the dominant internationalization patterns of the German political economy within the European division of labor: away from Southern Europe and France and towards Eastern Europe and the Emerging Markets.